2020
DOI: 10.1089/jpm.2018.0647
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of an Ambulatory Kidney Palliative Care Program

Abstract: Background: Many patients with serious kidney disease have an elevated symptom burden, high mortality, and poor quality of life. Palliative care has the potential to address these problems, yet nephrology patients frequently lack access to this specialty. Objectives: We describe patient demographics and clinical activities of the first 13 months of an ambulatory kidney palliative care (KPC) program that is integrated within a nephrology practice. Design/Measurements: Utilizing chart abstractions, we characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 19 publications
1
47
1
Order By: Relevance
“…Interviewed patients were seen in the clinic a range of 1 to 4 or more visits prior to their interview. The sample population was representative of the general clinic population 19 as most were of advanced age (median age: 67; range: 46-97) and male gender, with approximately 90% having CKD stage V. All individuals on renal replacement therapy (n ¼ 5) were receiving hemodialysis (HD). All the patients interviewed (n ¼ 8) were male, while the all caregivers interviewed were female (n ¼ 3, 2 daughters and 1 spouse).…”
Section: Participant Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviewed patients were seen in the clinic a range of 1 to 4 or more visits prior to their interview. The sample population was representative of the general clinic population 19 as most were of advanced age (median age: 67; range: 46-97) and male gender, with approximately 90% having CKD stage V. All individuals on renal replacement therapy (n ¼ 5) were receiving hemodialysis (HD). All the patients interviewed (n ¼ 8) were male, while the all caregivers interviewed were female (n ¼ 3, 2 daughters and 1 spouse).…”
Section: Participant Demographicsmentioning
confidence: 99%
“…We previously described patient demographics and clinical activities of an integrated ambulatory nephrology and palliative care clinical program at our institution called The Kidney CARES (Comprehensive Advanced Renal disease and ESRD Support) Program. 19 We now present findings from an exploratory qualitative study of patient and caregiver perceptions of the clinic. The objectives of this work are to identify the perceived value and impact of the clinic, the palliative care needs of a patient population that would attend the clinic and facilitators or barriers to care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies conducted in patients with kidney disease and in other populations support the feasibility and effectiveness of engaging patients and families in advance care planning. 42 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 That a substantial proportion of participants herein who did not want to be resuscitated had documented neither a surrogate decision maker nor treatment preferences illuminates an important gap in care. A default approach to resuscitation in many health care systems makes these patients especially vulnerable to receiving care that is incongruent with their preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care consultation has been associated with improvement in symptom burden in other populations 36 , 65 but is underused for patients receiving maintenance dialysis. 15 , 66 Although little is known about the feasibility, acceptability, and effectiveness of enhancing palliative care support for patients receiving maintenance dialysis, 52 , 55 , 67 the very high prevalence of palliative care needs and symptom burden among these individuals highlights the potential value of efforts to improve their access to palliative care. 58 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 …”
Section: Discussionmentioning
confidence: 99%
“…Emerging models of care demonstrate that integration of palliative care within nephrology practices can help promote conservative kidney management and advance care planning and also improve patient satisfaction among older patients; however, implementation has proved to be challenging [8,9]. Previous research has demonstrated numerous clinician barriers to providing conservative kidney management and facilitating advance care planning including prognostic uncertainty, inconsistent collaboration between nephrologists and primary care physicians (PCP), and limited knowledge of ESRD treatment options [10][11][12].…”
Section: Introductionmentioning
confidence: 99%